1995
DOI: 10.1037/0033-295x.102.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Implicit social cognition: Attitudes, self-esteem, and stereotypes.

Abstract: Social behavior is ordinarily treated as being under conscious (if not always thoughtful) control. However, considerable evidence now supports the view that social behavior often operates in an implicit or unconscious fashion. The identifying feature of implicit cognition is that past experience influences judgment in a fashion not introspectively known by the actor. The present conclusionthat attitudes, self-esteem, and stereotypes have important implicit modes of operation-extends both the construct validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

112
3,776
7
142

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 5,210 publications
(4,037 citation statements)
references
References 274 publications
(303 reference statements)
112
3,776
7
142
Order By: Relevance
“…The term implicit refers to hypothetical psychological attributes that are introspectively inaccessible but that can be assessed through reaction times, word associations, or other non-self-report measures. Thus, SE can be either a deliberate evaluation of self (explicit SE) [17] or an impulsive, automatic, and overlearned evaluation (implicit SE) [18]. Implicit SE and explicit SE are considered to be relatively enduring characteristics, shaped by both positive and negative experiences [17] and [19].…”
Section: Introductionmentioning
confidence: 99%
“…The term implicit refers to hypothetical psychological attributes that are introspectively inaccessible but that can be assessed through reaction times, word associations, or other non-self-report measures. Thus, SE can be either a deliberate evaluation of self (explicit SE) [17] or an impulsive, automatic, and overlearned evaluation (implicit SE) [18]. Implicit SE and explicit SE are considered to be relatively enduring characteristics, shaped by both positive and negative experiences [17] and [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the theoretical importance of this issue, little research has simultaneously examined the perception of race and expression. Instead, the majority of previous research has examined these cues in isolation, independent of one another; research on race perception typically examines responses to faces with emotionally neutral expressions (e.g., Devine, Plant, Amodio, Harmon-Jones, & Vance, 2002;Levin, 2000;Greenwald & Banaji, 1995), and research on emotional expression often examines responses to faces depicting only one race (typically Caucasian) (e.g., Eimer, Holmes, & McGlone, 2003;Hansen & Hansen, 1988). While it is necessary to investigate the independent effects of these cues, they are typically perceived simultaneously, making it important to understand how the cues are perceived in combination throughout processing.…”
mentioning
confidence: 99%
“…On the contrary, the activation of attitudes and stereotypes, though clearly fast and effortless, shows too large an inter-subject variability to be seen as merely automatic (e.g., Devine & Sharp, 2009 In effect, what an abundance of studies has reported (see, e.g., Greenwald & Banaji, 1995;Payne & Gawronski, 2010) is that these higher thought processes are often unconscious, but this does not allow us to speak straightforwardly of automatisms (e.g., Dijksterhuis, 2010). Even when automaticity does appear to be allied with unconscious processing, it is so in more than one way or degree (Bargh, 1989;.…”
Section: Main Issuesmentioning
confidence: 99%
“…The change of focus in unconscious social cognition from automatic behavior to implicit cognition can be attributed to Greenwald and Banaji (1995). In this paper, the authors surveyed the main constructs of social psychology, to wit, attitudes, stereotypes, and self-esteem, from the unifying viewpoint of implicit construct, "the introspectively unidentified (or inaccurately identified) trace of past experience that mediates R" (Greenwald & Banaji, 1995, p. 5), where R names categories of responses.…”
Section: Implicitness Vs Explicitness In Social Psychologymentioning
confidence: 99%